A systematic review and meta-analysis on the management of concomitant abdominal aortic aneurysms and renal tumours. (August 2022) - Lawrie, Katerina; Whitley, Adam; Balaz, Peter
Objectives: The treatment of concomitant abdominal aortic aneurysms and renal tumours is controversial. The aim of this study was to ascertain which of the following three strategies, one-stage open aneurysm repair and nephrectomy, two-stage open aneurysm repair and nephrectomy or two-stage endovascular aneurysm repair and nephrectomy, is the best approach. Methods: systematic review and meta-analysis of articles published between January 1992 and April 2021 describing the treatment of concomitant abdominal aortic aneurysms and renal tumours. Results: A total of 1168 records were identified. After the selection process, 12 studies with data on 89 patients were included. Sixty-two patients underwent one-stage open procedures, 18 patients underwent two-stage open procedures and nine underwent two-stage endovascular procedures. The overall postoperative mortality was 0.82% (95% CI, 0.00–4.61). The postoperative mortality for one-stage open procedures was 3.09% (95% CI, 0.00–10.11). No deaths occurred in the postoperative period open two-stage procedures or two-stage endovascular procedures. The weighted postoperative morbidity for all procedures was 23.86% (95% CI, 12.64–35.08) and for open one-stage procedures was 37.40% (95% CI, 14.33–60.47). Data concerning postoperative complications of two-stage open procedures were extractable from only one patient in whom no complications were reported. Two postoperative complications were reported after two-stage endovascular procedures from a total of six patients with extractable postoperative data. We were unable to perform meta-analysis on long-term outcomes as the data were reported non-uniformly. Conclusion: There is currently no evidence to suggest that any procedure is associated with better outcomes. However, a one-stage open approach was the most commonly used option, favoured as it avoids delaying treatment of either of the conditions. Two-stage open procedures were preferred in cases where the surgical risk of a one-stage procedure was higher than the potential benefit. For such cases, two-stage endovascular repair is becoming more popular as a less invasive approach.